KETERDEDAHAN INFORMASI BENCANA DAN KESIAPSIAGAAN MASYARAKAT MENGHADAPI BENCANA BANJIR ROB DI KABUPATEN ACEH BARAT - Farina Islami; Yuhdi Fahrimal; Asmaul Husna; Putri Maulina (Jurnal Media dan Komunikasi Indonesia, 2023)
The research objective is to analyze the influence of individual characteristics and disclosure of disaster risk information on community preparedness in facing coastal floods. The methodology used is explanatory research with a quantitative approach. In this study, a questionnaire was used with the number of samples were 82 respondents who were in the desa Pasir, Kec. Johan Pahlawan, Kab.Aceh Barat. The results of this study indicate that the individual characteristics of gender, age, and final education have a significant effect on community preparedness to face coastal flooding, but are classified as quite weak. Meanwhile, the disclosure of disaster risk information, namely the intensity of media use, the frequency of media use, and the quality of information has a significant effect on community preparedness to face coastal flooding, and is classified as strong.